PENGARUH BUDAYA LOKAL DALAM PILIHAN PENGGUNAAN KATA SAPAAN BERBAHASA INGGRIS - Ike Revita (Universitas Andalas, 2013)
This writing is aimed at describing the phenomena of terms of address used by English Department Students when they are interacting with their lecturers in the class. Two main problems are analysed here, (1) the forms of the terms of address used by English Depratment Students and (2) the influence of l terms of addreoca culture in choosing the form of the terms to address their lecturers in class interaction. Data are the terms of address used by English Department Students who are taking and already have taken Pragmatics Course. The data are takan by observational method, recording, note-taking, and interviewing technique. Pragmatic, Referential, and Translational Identity methods are used to analyze the data by applying the concept of terms of address proposed by Holmes (1992) and context Yule (1996). The result of analysis is presented descriptively. Having been analyzed, it is found that there are five forms of terms used by English Department Students to address their lecturers. They are (1) GU+GP+NP; (2) GK+NP; (3) GU+NP; (4) GH+NP; and (5) Bunda. The local culture that influences the choices of this terms of address are (1) raso jo pareso and (2) malu jo sopan.